Stabilisasi Tanah Lempung Dengan Pasir Bermacam Gradasi Dan Campuran Kapur - M. Shoffar Al Hafizh; Gunawan Wibisono; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Unconfined compression strength and CBR values of sandy clay are influenced by several factor such as sand and clay content, soil properties, density, moisture content, and gradation. This research tries to figure out the effect of sandy clay gradation on its unconfined compression strength and CBR values. Sandy clay mixtures were made from different percentage of sand and clay fractions. Sand fraction gradation varied from well to poor (gap). Clay was also stabilized with quick lime. The results of this research indicated that the addition of sand and lime into clay increased unconfined compression strength and CBR values, especially after 28 days curing time. The largest value of unconfined compression strength test occurred at mixture with 70% clay, due to the cohesiveness obtained from clay and lime stabilisation. The largest CBR values were found in the mixture with less contained clay.Keywords: unconfined compression strength,CBR, gradation, density, sand, clay